Rwanda : Staff Report for the 2017 Article IV Consultation, Seventh Review Under the Policy Support Instrument, and Second Review Under the Standby Credit Facility- Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Rwanda has demonstrated strong macroeconomic policy management and implemented an ambitious development strategy that has resulted in high and inclusive growth, lower poverty and more gender equality, and improved living standards. Growth in 2016 was 5.9 percent, down from 2015, but comparing favorably to growth in the subcontinent. A recovery of growth is expected in 2017-18, owing to good rains and expanding domestic production. A spike in consumer price inflation in early 2017 was driven by food prices. Main risks to economic growth continue to be weather shocks affecting agriculture, regional security issues, and unexpected shifts in external development assistance.